Detection of seven β2-agonists in teeth by LC-MS/MS: preliminary results. (International Journal of Health, Animal Science and Food Safety, 2016)
β2-agonists are powerful tocolytic (the only use permitted in cattle) and bronchodilator agents, butmay also be administered as growth promoters to improve the production of lean meat increasing alsothe lipolytic activity. Although the European Union (EU), China and other Asian countries have bannedthe use of β2-agonists for growth promoting purposes (European Union, 2003), the United States ofAmerica (USA) authorised ractopamine as a feed additive for swine, cattle and turkey. These veterinarydrugs, generally show high clearance rates in the conventional biological matrices, as well as urine, liverand muscle, making difficult their detection (Wu, 2014). For this reason, we suggested bovine teeth asa new unconventional matrix of accumulation in a more long-time window, for the detection ofcimaterol, clenbuterol, isoxsuprine, mabuterol, ractopamine, salbutamol and terbutaline. In literature,the few studies on teeth are limited to human (Andra, 2015) and are absent for veterinary medicine.The samples extracted by a simple liquid extraction step with ethyl acetate:tert-butyl methyl ether (4:1,v/v) after washing and pulverization of teeth, through a ball mill, were analysed using a liquidchromatography tandem mass spectrometry (LC-MS/MS) confirmatory method validated according tothe Commission Decision 2002/657/EC criteria (European Union, 2002). Teeth from 8 veal calves,administered per os with 80 mg day-1 oral ractopamine for 32 days, and from seven random bovinesfrom the food chain were collected at the slaughterhouse to test the suitability of this matrix. Theresults demonstrated ractopamine presence in teeth from the treated animals (average concentration8.90 ng g-1). Isoxsuprine was found in a control sample (13.67 ng g-1), demonstrating the effectivenessof this matrix as a powerful tool to ensure illegal treatment.
Keywords: Bovine; teeth; β2-agonists; Residues; HPLC-MS/MS.